The Butler Affair and the Geopolitics of Identity. (April 2013) - Kearns, Gerry
In the wake of the Global War on Terror, Judith Butler has written of the 'precarity' of life, of the inevitable vulnerability of one's life in the face of the actions of strangers. Refusing to accept this, the United States has developed a form of nationalism that claims invulnerability for its citizens while treating as expendable the lives of distant others who even unwittingly associate with those who threaten the US homeland. Butler has extended this set of criticisms to Israel's policy towards Palestinian people and in doing so has been criticised as anti-Semitic. She has engaged with these questions about Jewish identity, nationalism, and toleration through an engagement with writers of the Jewish diaspora, developing what we may describe as a geopolitical perspective on identity. The value of such a perspective was given ironic point by the public controversy over the award to Butler of the Adorno Prize in 2012. This paper argues also that in responding to the biopolitics of the Global War on Terror, Butler has elaborated on some of the geopolitical bases of identity and in doing so has illuminated the academic politics of the current Boycott, Divestment, and Sanctions campaign called for by many institutions of Palestinian civil society.